EMPLOYEE RETENTION STRATEGIES IN THE FACE OF ECONOMIC FLUCTUATIONS - Yusnaini; Mauli Siagian; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Retaining your best employees when the economy is unstable is not easy. Companies need special strategies to make their employees feel at home and productive. The study in this research uses the literature method. The results show that employee retention strategies include adjusting salaries and benefits, providing opportunities for employees to grow, improving employee welfare and creating a comfortable working atmosphere. These strategies not only make employees more loyal, but also help companies survive economic problems. In the end, companies that care about their employees will be stronger in the face of fierce business competition. In essence, taking good care of your employees is an important investment in your company's future.